Assessing the entrepreneurial management amongst Bahrain SMEs - Mohamed Shekar, Mohamed Jaafar; Hassan, Mazlan; Al Mubarak, Muneer (Human Resource Management Academic Research Society, 2021)
Entrepreneurship is widely regarded the catalyst of business prosperity and economies development. Accordingly, a high level of entrepreneurial management practices should lead to a high level of success, and vice versa. The entrepreneurial management construct (EM), conceptualized by Stevenson (1983) and operationalized by Brown et al. (2001), is centered on the business opportunity and meant to measure both the individuals’ and firms-level entrepreneurial behavior with regards to dealing with business opportunity in six dimensions; namely: growth orientation (GO), strategic orientation (SO), resource orientation (RO), management structure (MS), reward philosophy (RP), and entrepreneurial culture (EC). This study aims to verify the level of entrepreneurial management embraced by the small and medium sized enterprises (SMEs) in the kingdom of Bahrain. Based on the descriptive statistical analysis of 360 self-administered questionnaires, this study suggests that the vast majority of SMEs in Bahrain could be viewed as entrepreneurial. The dimensional investigations reveal that the SMEs propensity towards entrepreneurial management is at its most in the GO, followed by MS, then EC and RP, while it is slightly lesser in the SO and RO dimensions. This study contributes to the literature, empirically, by proving that the EM practices are applicable to any firm, regardless of its age, size, business activity, or ownership structure.